ANALISIS PENGARUH DPR, DER, ROE, DAN TATO TERHADAP HARGA SAHAM (Studi Kasus pada Perusahaan Industri Dasar dan Kimia yang Terdaftar di BEI Periode 2010-2014) - Nugraha, Rheza Dewangga; Sudaryanto, Budi (Faculty of Economics and Business Diponegoro University, 2016)
Every investor who want to invest in stock market, they need some information from related firm, both of the Financial reports and information about their activities which are going on and also recent price of stock. Thefore the investor can determine which firm’s stock is worthy to purchase in order be able to create better profit for that investor in the future. The research aimed to analyze the influence Dividend Payout Ratio, Debt to Equity Ratio, Return on Equity, and Total Asset Turnover. The population used in the study is all companies engaged in chemical and basic industry sectors in 2010-2014. Therefore total population obtained is 65 companies. Sampling in this study using purposive sampling which resulted in a sample into 26 companies chemical and basic industry sectors. Data analysis method used multiple linear regression analysis and using classical assumption test. Based on the research results, the result that dividend payout ratio (DPR), debt to equity ratio (DER), return on equity (ROE) and total asset turnover (TATO) on stock price with the regression coefficient is lgY = 2.933 + 0,266 DPR - 0,105 DER + 0,035 ROE - 0,282 TATO.